2013
DOI: 10.1002/pro.2342
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of HMG proteins and H1 with hybrid PNA–DNA junctions

Abstract: The objective of this study was to evaluate the effects of inserting peptide nucleic acid (PNA) sequences into the protein-binding surface of an immobilized four-way junction (4WJ). Here we compare the classic immobile DNA junction, J1, with two PNA containing hybrid junctions (4WJ-PNA 1 and 4WJ-PNA 3 ). The protein interactions of each 4WJ were evaluated using recombinant high mobility group proteins from rat (HMGB1b and HMGB1b/R26A) and human histone H1. , while 4WJ-PNA 1 does not. Circular dichroism spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…The interaction between HMGB1 and linker histones (H1 and H5) occurs through their acidic and basic tails, respectively (Cato et al, 2008). This interaction between HMGB1 and H1 facilitates DNA-protein complex formation (Totsingan and Bell, 2013), DNA ligation reactions (Yamanaka et al, 2002) and enables stress-induced gene silencing (e.g., pro-inflammatory cytokine TNF-α) (El Gazzar et al, 2009). The interaction between HMGB1 and H1 is regulated by pH, local ionic concentration, and redox state (Kohlstaedt and Cole, 1994b; Kohlstaedt et al, 1987).…”
Section: Hmgb1 Functionmentioning
confidence: 99%
“…The interaction between HMGB1 and linker histones (H1 and H5) occurs through their acidic and basic tails, respectively (Cato et al, 2008). This interaction between HMGB1 and H1 facilitates DNA-protein complex formation (Totsingan and Bell, 2013), DNA ligation reactions (Yamanaka et al, 2002) and enables stress-induced gene silencing (e.g., pro-inflammatory cytokine TNF-α) (El Gazzar et al, 2009). The interaction between HMGB1 and H1 is regulated by pH, local ionic concentration, and redox state (Kohlstaedt and Cole, 1994b; Kohlstaedt et al, 1987).…”
Section: Hmgb1 Functionmentioning
confidence: 99%
“…In our previous study, EMSAs were used to measure the binding constants of 4WJ-PNA 1 and 4WJ-PNA 3 toward HMGB1b. This report showed that the protein binds 4WJ-PNA 3 with a nearly identical affinity to J1 (K D ~ 6.0 μM) and 4WJ-PNA 1 slightly less (K D ~ 16.0 μM) 18 . Moreover, these data show that the insertion of a PNA strand into the immobilized lattice of J1 does not abolish protein recognition.…”
Section: Resultsmentioning
confidence: 75%
“…Three hybrids, 4WJ-PNA 1 , 4WJ-PNA 3 and 4WJ-PNA 1,3 , contain shorter PNA strands relative to the DNA strands (12 vs. 16) in order to minimize synthetic problems associated with longer PNA sequences (Figure 2A). In our previous study we show that the DNA overhangs, present in 4WJ-PNA 1 and 4WJ-PNA 3 , do not prohibit the formation of immobilized junctions because the non-bonded regions are not located close to the junction branch point 18 . To avoid overhanging DNA residues, three hybrids were designed with shorter (blunt) DNA strands: b 4WJ-PNA 1 , b 4WJ-PNA 3 and b 4WJ-PNA 1,3 .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The data are based on the protocol used by Kallenbach and Seaman to characterize, J1 [2] , [3] . In our previous study, each hybrid PNA–DNA 4WJ is evaluated vs. J1 [4] .…”
Section: Datamentioning
confidence: 99%